Predicting response to benralizumab in chronic obstructive pulmonary disease: analyses of GALATHEA and TERRANOVA studies. Issue 2 (February 2020) - Criner, Gerard J; Celli, Bartolome R; Singh, Dave; Agusti, Alvar; Papi, Alberto; Jison, Maria; Makulova, Natalya; Shih, Vivian H; Brooks, Laura; Barker, Peter; Martin, Ubaldo J; Newbold, Paul
Summary: Background: Benralizumab did not significantly reduce exacerbations compared with placebo in the phase 3 GALATHEA and TERRANOVA trials of benralizumab for patients with chronic obstructive pulmonary disease (COPD). We aimed to identify clinical and physiological characteristics of patients with COPD that could help to identify people who are likely to have the greatest treatment effect with benralizumab. Methods: We analysed individual study and pooled results from GALATHEA and TERRANOVA. At study enrolment, patients from GALATHEA and TERRANOVA were aged 40–85 years, had moderate to very severe airflow limitation, had elevated blood eosinophil counts, and at least two exacerbations or one severe exacerbation in the previous year despite dual inhaled therapy (inhaled corticosteroids plus long-acting β2 -agonists or long-acting β2 -agonists plus long-acting muscarinic antagonists) or triple inhaled therapy (inhaled corticosteroids plus long-acting β2 -agonists plus long-acting muscarinic antagonists). We analysed data for 3910 patients who received benralizumab (30 mg or 100 mg subcutaneously every 8 weeks; first three doses every 4 weeks) or placebo with dual or triple therapy to identify factors consistently associated with annual exacerbation rate reduction. We evaluated the annual exacerbation rate for benralizumab versus placebo as the primary endpoint. GALATHEA and TERRANOVA are registered with ClinicalTrials.gov, NCT02138916 and NCT02155660, respectively. Findings: For 2665 patients with elevated blood eosinophil counts, treatment effect with benralizumab every 8 weeks at 100 mg, but not at 30 mg, occurred for patients with a history of more frequent exacerbations, poorer baseline lung function, or greater baseline lung function improvement with short-acting bronchodilators. Patients with baseline blood eosinophil counts of 220 cells per μL or greater with: three or more exacerbations in the previous year receiving benralizumab every 8 weeks versus placebo, had rate ratios (RRs) of 0·69 (95% CI 0·56–0·83) for 100 mg and 0·86 (0·71–1·04) for 30 mg; postbronchodilator FEV1 of less than 40% had RRs of 0·76 (0·64–0·91) for 100 mg and 0·90 (0·76–1·06) for 30 mg; and postbronchodilator response of at least 15% had RRs of 0·67 (0·54–0·83) for 100 mg and 0·87 (0·71–1·07) for 30 mg. When combined factors were examined, patients with elevated baseline blood eosinophil counts, with three or more exacerbations in the previous year, and who were receiving triple therapy were identified as likely to benefit from benralizumab 100 mg every 8 weeks versus placebo (RR 0·70 [95% CI 0·56–0·88]). Benralizumab 30 mg every 8 weeks did not benefit patients meeting these criteria compared with placebo (RR 0·99 [95% CI 0·79–1·23]). Interpretation: Elevated blood eosinophil counts combined with clinical characteristics identified a subpopulation of patients with COPD who had reductions in exacerbations with benralizumab treatment. These hypothesis-generating analyses identified the potential efficacy of benralizumab 100 mg for this subpopulation. These findings require prospective evaluation in clinical trials. Funding: AstraZeneca.